PEMBELAJARAN PROBLEM BASED LEARNING BERPENDEKATAN SOCIO-SCIENTIFIC ISSUE BERBANTUAN BULETIN UNTUK MENINGKATKAN BERPIKIR KRITIS SISWA - Fitroty, Ismy Yahdillah; Wahyuni, Eva Ari; Ahied, Mochammad; Hartiningsih, Try; Rakhmawan, Aditya (Natural Science Education Research, 2023)
The purpose of this study is to determine the improvement of students' critical thinking skills towards Problem Based Learning learning with a bulletin-assisted Socio-Scientific Issue approach. Sampling using Purposive Sampling technique, namely class at VII A students as many as 20 students as experimental class and VII C as many as 18 students as control class which was carried out at MTs. Masyhudiyah, Gresik. The research method used is quasi experimental design in the form of nonequivalent control group design. The data analysis technique using the Mann Whitney test is 0.002 less than 0.05 which means there is a difference in students' critical thinking skills between the experimental class and the control class. Increasing students' critical thinking skills was carried out using the N-Gain test, which was 0.68 in the experimental class and 0.41 in the control class, which means that students' critical thinking skills using Problem Based Learning with a bulletin-assisted Socio-Scientific Issue approach in the experimental class were better than conventional learning in the control class.